Clinical Characteristics According to Age and Duration of Symptoms to Be Considered for Rapid Diagnosis of Pediatric Intussusception - Park, In Kyu; Cho, Min Jeng (Frontiers in Pediatrics, 2021)
Purpose: The purpose of this study was to evaluate whether clinical findings in children with ileocolic intussusception differ based on age and duration of symptoms and to assess the clinical characteristics of diagnosed and undiagnosed patients to determine which symptoms make diagnosis more difficult. Methods: We reviewed 536 medical records of <15-year-old children diagnosed with ileocolic intussusception between 2008 and 2019. We divided the children into three categories according to age (<1 year, 1–2 years, and ≥2 years). The children were also divided into two groups based on whether symptoms lasted for more or less than 6 h. Diagnosed and undiagnosed children were assessed separately during for the initial evaluation. Results: Following analysis of the three age groups, bloody stool, post-enema bloody stool, diarrhea, vomiting, poor oral intake, and lethargy were more frequent in children aged <1 year. In children aged ≥2 years, non-specific abdominal pain was more frequent and the undiagnosed rate was higher. Following analysis of the duration of symptoms, paroxysmal pain was significantly more frequent in the early group (<6 h), and bloody stool and fever were significantly more frequent in the late group (≥6 h). Nonspecific abdominal pain was more frequent and the door-to-diagnosis time was significantly longer in the undiagnosed group than in the diagnosed group. Conclusions: Clinical findings of ileocolic intussusception vary depending on the age and duration of symptoms. Younger children with paroxysmal pain, vomiting, bloody stool, poor oral intake, or lethargy should be suspected of having intussusception. In older children, nonspecific abdominal pain without bloody stool may be a symptom of intussusception. Glycerin enema is helpful in diagnosing intussusception in children with no typical symptoms.